FORENSIC ANALYSIS FOR WATER TURBINE USING FMEA METHOD - Nata Prama, Timothy
Water is a source of renewable energy. To harness this energy, a system known as a Hydroelectric Power Plant (PLTA) is required. Within a PLTA, there is a device called a water turbine, which has a risk of failure. To study these failures, a process called forensic analysis is conducted. Forensic analysis of water turbines has been performed using methods such as fishbone diagrams or failure trees. However, these methods do not provide numerical results. In this Final Project, the method being used is Failure Mode and Effect Analysis (FMEA). The FMEA method provides numerical values for severity, occurrence, detection, and the Risk Priority Number (RPN). This Final Project summarizes the failures and failure factors of the Francis water turbine as a system and its subsystems, including runner, turbine shafts, guide bearings, draft tubes, spiral cases, and guide vane. The project includes values for severity, occurrence, detection, and RPN. These values can indicate the reliability of the device. The lower the RPN value, the more reliable the device is. For cases with high RPN values, recommendations are made to reduce the RPN value. The highest RPN in water turbine system is 128, with value of severity at 8, occurrence at 3, and detection at 4,